Atrial-paced, exercise-similar heart rate envelope induces myocardial protection from ischaemic injury. Issue 6 (18th November 2021) - Zhu, Zhiyong; Gao, Zhan; Chen, Biyi; Hall, Duane D; Minerath, Rachel; Koval, Olha; Sierra, Ana; Subbotina, Ekaterina; Zhu, Xiaoyi; Kim, Young Rae; Yang, Jun; Grumbach, Isabella; et al.
Abstract: Aims: The study investigates the role and mechanisms of clinically translatable exercise heart rate (HR) envelope effects, without dyssynchrony, on myocardial ischaemia tolerance compared to standard preconditioning methods. Since the magnitude and duration of exercise HR acceleration are tightly correlated with beneficial cardiac outcomes, it is hypothesized that a paced exercise-similar HR envelope, delivered in a maximally physiologic way that avoids the toxic effects of chamber dyssynchrony, may be more than simply a readout, but rather also a significant trigger of myocardial conditioning and stress resistance. Methods and results: For 8 days over 2 weeks, sedated mice were atrial-paced once daily via an oesophageal electrode to deliver an exercise-similar HR pattern with preserved atrioventricular and interventricular synchrony. Effects on cardiac calcium handling, protein expression/modification, and tolerance to ischaemia–reperfusion (IR) injury were assessed and compared to those in sham-paced mice and to the effects of exercise and ischaemic preconditioning (IPC). The paced cohort displayed improved myocardial IR injury tolerance vs. sham controls with an effect size similar to that afforded by treadmill exercise or IPC. Hearts from paced mice displayed changes in Ca 2+ handling, coupled with changes in phosphorylation of calcium/calmodulin protein kinase II, phospholamban and ryanodine receptor channel, and transcriptional remodelling associated with a cardioprotective paradigm. Conclusions: The HR pattern of exercise, delivered by atrial pacing that preserves intracardiac synchrony, induces cardiac conditioning and enhances ischaemic stress resistance. This identifies the HR pattern as a signal for conditioning and suggests the potential to repurpose atrial pacing for cardioprotection. Graphical abstract: